CLIMATE MIGRATIONS: THE ROLE OF HUMAN RIGHTS TO OVERCOME THE PERSISTENT LEGAL VACUUM - Pérez, Beatriz Felipe (2019)
The impacts of climate change affect, directly and indirectly, patterns of human mobility. In fact, there are already examples of so-called climatic migrations around the entire planet. Cross-border climate migrations are especially relevant, as one of the most serious problems faced by people fleeing their countries due to climate change, along with other reasons, is the limited recognition of their situation by international law and, consequently, the lack of legal protection. Given this gap, the current article analyzes the possible application of international human rights law, in two ways, on the one hand, as a basic guarantee of the fundamental rights of these people and, on the other, as a basis for demanding responsibility of pollutant States, in face of the human rights violations experienced by climate migrants.